Impacts generated by the inspection of excess weight in commercial vehicles on the BR-153 highway in Gurupi – TO (Research, Society and Development, 2021)
In this article, the impacts generated by the inspection of excess weight in commercial vehicles on the BR153 highway in the municipality of Gurupi / TO are addressed. There is a great dependence of the industry on road transport, the inconsistencies of the national inspection system, the need to collect traffic data for decision making, the dimensioning of a new pavement or reinforcement taking into account the number “N” That represents the parameter of the traffic request to the pavement. In the study, it is concluded that excess weight in commercial vehicles is one of the main factors in the destruction of Brazilian highways and in the considerable decrease in useful life. And, finally, the impacts of the inspection of excess weight were evidenced, such as the reduction of the degradation of the pavement and the prevention of accidents caused by the traffic of overweight trucks.